2007
DOI: 10.1016/j.ijgo.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent versus sequential methods for labor induction at term

Abstract: The concurrent method of induction of labor resulted in shorter induction to delivery time and a higher proportion of vaginal deliveries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Although some studies have not observed a statistically significant increase in excessive uterine activity with their concurrent use, this is likely due to the small number of patients in these studies, differences in methodology (eg, uterine activity was not continuously monitored), and the relatively low frequency of this adverse event. [28][29][30] In one such trial, the frequency of uterine tachysystole with concurrent dinoprostone and oxytocin administration was 14% versus 5% with oxytocin alone (P ¼ .20). 28 The incidence of meconium passage and mean blood loss were similar in the two groups, further confirming the safety of both treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have not observed a statistically significant increase in excessive uterine activity with their concurrent use, this is likely due to the small number of patients in these studies, differences in methodology (eg, uterine activity was not continuously monitored), and the relatively low frequency of this adverse event. [28][29][30] In one such trial, the frequency of uterine tachysystole with concurrent dinoprostone and oxytocin administration was 14% versus 5% with oxytocin alone (P ¼ .20). 28 The incidence of meconium passage and mean blood loss were similar in the two groups, further confirming the safety of both treatments.…”
Section: Discussionmentioning
confidence: 99%